Lifetime measurements in 104Pd. (29th October 2020) - Majumder, C; Sharma, H P; Chakraborty, S; Tiwary, S S; Singh, R P; Muralithar, S; Bala, Indu; Bhattacharjee, S S; Garg, R; Neelam; Sharma, A; Rao, P V Madhusudhana
Abstract: High spin states in 104 Pd were populated via 94 Zr( 13 C, 3n γ ) fusion-evaporation reaction at a beam energy of 55 MeV. The Indian National Gamma Array was utilized to detect the de-exciting γ -rays. Lifetimes of states in the negative parity bands have been determined using the Doppler shift attenuation method. The present lifetime results suggest a moderate quadrupole deformation ( β 2 ≈ 0.2) for the negative parity bands. The Woods–Saxon total Routhian surface calculations have also been carried out which predicted a similar deformation for these bands. In addition, lifetimes of states in the positive parity band have also been determined. Present results found in agreement with the earlier reported values of lifetimes and hence agreed with the antimagnetic rotational character of the band as interpreted earlier.